From world religions to axial civilizations and beyond - Arjomand, Said Amir; Kalberg, Stephen (State University of New York Press, 2021)
"Essays in the field of comparative world religions and corresponding axial civilizations"-- Provided by publisher
Keywords: Religion and civilization.; Civilization -- Philosophy.; Religion et civilisation.; Civilisation -- Philosophie.; SOCIAL SCIENCE / Sociology of Religion.; Civilization -- Philosophy; Religion and civilization